Advances in 3D Printing for Electrochemical Energy Storage Systems (Journal of Material Science and Technology Research, 2021)
In the current scenario, energy generation is relied on the portable gadgets with more efficiency paving a way for new versatile and smart techniques for device fabrication. 3D printing is one of the most adaptable fabrication techniques based on designed architecture. The fabrication of 3D printed energy storage devices minimizes the manual labor enhancing the perfection of fabrication and reducing the risk of hazards. The perfection in fabrication technique enhances the performance of the device. The idea has been built upon by industry as well as academic research to print a variety of battery components such as cathode, anode, separator, etc. The main attraction of 3D printing is its cost-efficiency. There are tremendous savings in not having to manufacture battery cells separately and then assemble them into modules. This review highlights recent and important advances made in 3D printing of energy storage devices. The present review explains the common 3D printing techniques that have been used for the printing of electrode materials, separators, battery casings, etc. Also highlights the challenges present in the technique during the energy storage device fabrication in order to overcome the same to develop the process of 3D printing of the batteries to have comparable performance to, or even better performance than, conventional batteries.